Evaluation of fit for 3D-printed retainers compared with thermoform retainers - Cole, David; Bencharit, Sompop; Carrico, Caroline K.; Arias, Andrew; Tüfekçi, Eser (American journal of orthodontics and dentofacial orthopedics, 2019)
In the literature, there is little information available on 3D-printed orthodontic retainers. This study examined the accuracy of 3D-printed retainers compared with conventional vacuum-formed and commercially available vacuum-formed retainers. Three reference models (models 1, 2, and 3) were used to fabricate traditional vacuum-formed, commercially available vacuum-formed, and 3D-printed retainers. For each model, retainers were made using the 3 methods (a total of 27 retainers). To determine the trueness, ie, closeness of a model to a true model, the distance between the retainer and its digital model at reference points were calculated with the use of engineering software. The measurements were reported as average absolute observed values and compared with those of the conventional vacuum-formed retainers. Average differences of the conventional vacuum-formed retainers ranged from 0.10 to 0.20 mm. The commercially available and 3D-printed retainers had ranges of 0.10 to 0.30 mm and 0.10 to 0.40 mm, respectively. The conventional vacuum-formed retainers showed the least amount of deviation from the original reference models and the 3D-printed retainers showed the greatest deviation. However, all 3 methods yielded measurements within 0.5 mm, which has previously been accepted to be clinically sufficient. •The traditional vacuum-formed retainers had the least amount of deviation from the original model.•3D-printed retainers are good alternatives to the traditional vacuum-formed retainers.•Retainers may be successfully 3D printed with the use of stereolithography technology.